3. Extracorporeal membrane oxygenation for Covid-19 associated severe acute respiratory distress syndrome - Trang, Tran Huyen; Thanh, Nguyen Tat; Nguyen, Nguyen Minh; Dung, Nguyen Anh; Hai, Hoang Bui (Tạp chí Nghiên cứu Y học, 2022)
COVID-19 caused significant mortality worldwide, including in Vietnam. This study aimed to evaluate the effectiveness of Extracorporeal membrane oxygenation (ECMO) in the treatment of COVID-19 patients with acute respiratory distress syndrome (ARDS). From January 1, 2022 to March 31, 2022, the COVID-19 hospital admitted 395 critical patients, including 10 patients required veno-venous Extracorporeal membrane oxygenation (VV-ECMO). This descriptive study revealed relatively high survival rate of 60% (6/10 patients) with the median duration of ECMO was 11.5 days. The study group's SOFA and RESP scores were 6 and 4, respectively. Time from symptom onset to mechanical ventilation, duration of NIV and/or HFNC before mechanical ventilation, time from symptom onset to ECMO of the study patients were 9.5, 0 and 11.5 days, respectively. The most common complication in ECMO patients was nosocomial infection (70%), in addition to bleeding, embolism, or both at the same time. This preliminary research showed that ECMO was effective in the management of acute respiratory distress syndrome in patients with COVID-19.